Analisis Perbandingan Persediaan Optimum dengan Metode Lot for Lot, Period Order Quantity dan Economic Part Period - Rini, Monanda Wandita; Ananda, Nessa (Politeknik ATI Padang, 2021)
PT. X is a company engaged in the production of electrical and electronic equipment, one of its products is camera. This research aims to compare the inventory policies that have been implemented by the company with other dynamic deterministic models. In the production process, the company uses a stock policy with the Lot for Lot (LFL) method, but the total costs incurred by the company and the frequency of ordering are still quite high. This research aims to compare the inventory policies that have been implemented by the company with other dynamic deterministic models, such as Period Order Quantity (POQ) and Economic Part Period (EPP) methods so that the optimal inventory method can be determined. The results of this study indicate that the Economic Part Period (EPP) is the optimal method with a total cost of Rp. 69,284,600 and the order frequency is 7 times